Dendrobium nagataksaka (Orchidaceae: Epidendroideae), A New Species of Section Spatulata From Papua, Indonesia - Metusala, Destario (Phytotaxa, 2019)
Dendrobium nagataksaka, a new species of Dendrobium section Spatulata (Orchidaceae: Epidendroideae) from Papua, Indonesian New Guinea, is described and illustrated. The flower of this new species is morphologically close to Dendrobium gouldii, but differs in having longer midlobe relative to the sidelobes which it is as long as the sidelobes, a different shape midlobe, and a different shape keels on lip.